The Psychological State of Teachers During the COVID-19 Crisis: The Challenge of Returning to Face-to-Face Teaching - Ozamiz-Etxebarria, Naiara; Berasategi Santxo, Naiara; Idoiaga Mondragon, Nahia; Dosil Santamaría, María (Frontiers in Psychology, 2021)
Schools in Spain were closed in March 2020 to prevent the spread of COVID-19. In September 2020 most schools and universities in Spain reopened and teachers felt great uncertainty due to this unprecedented situation. Teachers have accumulated psychological symptoms since the beginning of the pandemic. During the lockdown they had to introduce online teaching and in view of the reopening of schools they have shown great concern for the new unprecedented teaching situation. The present study aims to measure the symptomatology shown by teaching staff in the Basque Autonomous Community at the time when schools were reopened. To do this, we recruited a sample of 1633 teachers who were given an online questionnaire which, in addition to collecting socio-demographic data, measured stress, anxiety and depression using the DASS-21scale. The results revealed that a high percentage of teachers showed anxiety, depression and stress symptoms. Furthermore, variables such as gender, age, job stability, the level of education at which they teach and parental status also influence this symptomatology. We argue for the need to safeguard the mental health of teachers in order to improve both the quality of teaching and the mental health of students.